Developing and Standardizing a Test to Evaluate Complex Skill Performance (Holding, Pushing, Pulling, Spinning, and Balance)In Freestyle Wrestling Players Aged (17-20) Years (Al-Muthanna Journal of Sport Education Sciences, 2026)
The importance of this research lies in its contribution to developing and standardizing an objective, scientific test to measure complex skill performance in freestyle wrestling players aged (17-20) years, in accordance with the requirements of real-world competition performance. This test also provides coaches and instructors with an accurate tool that can be relied upon to evaluate players' levels, diagnose their strengths and weaknesses, and guide training programs more effectively. The research problem was: A lack of standardized scientific tests capable of evaluating complex skill performance that combines holding, pushing, pulling, spinning, and balance skills within a single, integrated framework was observed. The absence of such tests makes it difficult to determine the true skill level of wrestlers and limits coaches' ability to accurately diagnose strengths and weaknesses. This negatively impacts the direction of training programs and the development of technical performance in a systematic and scientific manner. Hence, the research problem lies in the need to develop and standardize an objective test that measures the complex skill performance of freestyle wrestlers aged 17-20 years, serving as an accurate scientific tool to contribute to evaluating the players' level. The research objectives were:1- To develop and standardize a test to evaluate the complex skill performance (holding, pushing, pulling, spinning, and balance) of freestyle wrestlers aged 17-20 years.2- To establish criteria and levels for a test to evaluate the complex skill performance (holding, pushing, pulling, spinning, and balance) of freestyle wrestlers aged 17-20 years. The descriptive approach was used with a survey method. The sample consisted of wrestlers aged 17-20 years. After designing the test and establishing the criteria and levels, the most important conclusions were reached: The test designed by the researcher is capable of revealing the level of evaluation of complex skill performance (holding, pushing, pulling, spinning, and balance) for wrestlers aged 17-20 years. The most important recommendation was: Adopting the current test as a means of revealing the level of evaluation of complex skill performance (holding, pushing, pulling, spinning, and balance) for wrestlers aged 17-20 years.